Pengembangan Aplikasi Web Rekam Medis Studi Kasus RSIA. Prof. Dr. H. M. Farid Makassar - Nur Afdaliyah Anwar; Bayu Priyambadha; Achmad Arwan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The hospital is a place of care, service, and recovery of illnesses as well as places of care, can also be a means of education and research. Maternal and Child Hospital (RSIA) when viewed from the hospital classification, is classified as a Type C hospital, where Type C hospitals only provide limited subspecialty medical services, in this case child health services and obstetrics and gynecological services. At RSIA. Prof. dr. H. M. Farid Makassar, in this case including patient registration and recording medical record data still using media worksheets. In addition, the report-making process is still carried out manually so as to make the processing of patient data less than optimal. To deal with these problems, a web-based medical record application with added features is built and search for medical record data to facilitate data processing at RSIA. Prof. dr. H. M. Farid and features to make periodic reports. This study uses the waterfall method and also a prototype in building medical record application software. Based on the tests carried out namely unit testing that produces valid values ​​for all test lines and validation tests that produce 100% valid values ​​in all test cases. While the compatibility testing tested using the SortSite tool shows that the system can run well in 9 of the 9 browser versions tested.